THE EXPERIENCES OF SIGHTED PEOPLE IN COMMON SOCIO-CULTURAL ACTIVITIES WITH BLIND PEOPLE - Kruckauskaite, Jolanta; Sadauskas, Justinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The organisation of joint hikes for the blind and sighted is a completely new and untouched topic, the study of which can help to discover unexpected results, to show the significance and benefits of such activities not only for the blind but also for the sighted, their perception, new inner experiences, discoveries. Joint socio-cultural activities are not only a medium for the empowerment of the disabled, but also the education of empathic members of society and the promotion of new programs. The aim of the research is to reveal the experiences of sighted people participating in joint hikes with blind people. Semi-structured interviews were used to collect qualitative data. The research participants were 8 sighted people who had participated in joint hikes with the blind people. Thematic analysis was conducted. The experiences of the sighted and the blind have revealed that joint walks “erase” all differences, all borders. Sighted people see and learn what visual impairment is, what kind of world blind people live in – this brings them even closer to their comrades and encourages the desire to extend their friendship.